2021
DOI: 10.1186/s12912-021-00751-8
|View full text |Cite
|
Sign up to set email alerts
|

Operating room nurses’ experiences of limited access to daylight in the workplace – a qualitative interview study

Abstract: Background The operating room nurse is, among other things, responsible for patient safety and maintaining an aseptic environment. For hygienic reasons unnecessary traffic in the operating room should be avoided, which may mean that the operating room nurse works long shifts without relief. Operating departments are usually separated, where there might be no daylight opportunities in the operating room. The purpose of the study was to describe operating room nurses’ experiences of limited acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(44 reference statements)
0
4
1
Order By: Relevance
“…Access to daylight and views of the outside were also appreciated by participants as clinicians usually work in enclosed work environments that rely solely on artificial light and are detached from the outdoors. Despite mounting evidence demonstrating how daylight and outdoor views are associated with indicators of staff health and well-being, including stress (Golvani et al, 2021; Mihandoust et al, 2021; Zadeh et al, 2014), our findings suggest that enough exposure to windows for staff is not provided in many healthcare facilities. Most attention is paid to the provision of windows in patient areas to induce several demonstrated benefits, such as reduced pain, improved mood, and faster recovery (C.-H. Wang et al, 2019), reduced length of stay (Chiu et al, 2018), and decreased number of negative behaviors (Bai, 2015).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Access to daylight and views of the outside were also appreciated by participants as clinicians usually work in enclosed work environments that rely solely on artificial light and are detached from the outdoors. Despite mounting evidence demonstrating how daylight and outdoor views are associated with indicators of staff health and well-being, including stress (Golvani et al, 2021; Mihandoust et al, 2021; Zadeh et al, 2014), our findings suggest that enough exposure to windows for staff is not provided in many healthcare facilities. Most attention is paid to the provision of windows in patient areas to induce several demonstrated benefits, such as reduced pain, improved mood, and faster recovery (C.-H. Wang et al, 2019), reduced length of stay (Chiu et al, 2018), and decreased number of negative behaviors (Bai, 2015).…”
Section: Discussioncontrasting
confidence: 73%
“…This is an essential factor to consider, especially in designing EDs where patients are not supposed to stay for more than a day. Instead, what is gained is boosted energy and stress relief (Golvani et al, 2021), improved sleep quality leading to increased alertness and productivity (Hittle & Wong, 2022; Zadeh et al, 2014), and burnout reduction among staff (Ziabari et al, 2023), leading to quality care for patients. Simulated daylight and natural views might be used for similar positive impacts where the actual interventions, such as windows, skylights, or outdoor patios, are impossible to be implemented (Engwall et al, 2015; Pati et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our findings align with a study conducted in the USA, where a substantial group of Certified Registered Nurse Anesthetists was surveyed regarding their occupational exposure to inhalational anesthetic agents, yielding quite similar results ( 5 ). The study demonstrated that exposure to waste anesthesia gases contributes to fatigue ( 9 , 17 ). Anesthetic gas pollution can arise from various sources, including anesthesia breathing circuits like pediatric T-piece circuits, especially in the absence of a proper scavenging system and the maintenance of the operating theatre ventilation system ( 5 ).…”
Section: Discussionmentioning
confidence: 98%
“…Patient safety has been shown to depend in part on addressing the sources of stress and exhaustion ( 8 ). For example, factors such as working in a closed environment, and limited access to sunlight which OR personnel routinely bear, contribute to fatigue ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…This can result in operating rooms being experienced as cold rooms for those working in them. As Golvani and Roos [11] described, access to daylight can lead to feelings of joy and a sense of time, whereas a lack thereof contributes to feelings of fatigue and stress among OR nurses. Moreover, perceived incompetence, lack of confidence, relational problems with regard to the surgeon, and team members' disruptive behaviour were described as sources of stress for OR nurses.…”
Section: The Physical Work Environmentmentioning
confidence: 99%